НОМІНАЦІЯ ПОБУТОВОЇ ЛЕКСИКИ В ГОВІРКАХ ПІВДНЯ УКРАЇНИ (Zaporizhzhia Historical Review, 2021)
The peculiarities of consumer goods presentation are investigated in this article. In particular, clothes, shoes and their elements, rooms, vegetable and animal world dealing with the man’s life activity are also considered in it. The problem of stylistic differentiation has been solved here.